Penggunaan berbagai jenis biochar dan jenis pupuk dalam meningkatkan pertumbuhan dan hasil tanaman jagung manis - Manase Wolu Praing; Yohanes Parlindungan Situmeang; Ida Bagus Komang Mahardika (Fakultas Pertanian, Universitas Warmadewa, 2018)
This study aims to determine the effect of giving biochar and the type of fertilizer and its interaction in increasing the growth and yield of sweet corn plants. Randomized group design (RBD) Factorial pattern 2 factors (type of biochar and type of fertilizer) were used in this study. The results showed that the coconut shell biochar treatment provided the highest wet weight with 97.82 g which increased by 61.93% when compared to without biochar 60.41 g. The NPK-compost fertilizer treatment gave the highest value of weighted cob weight, which was 101.22 g which was significantly different and increased by 23.27% and 13.59% when compared with NPK fertilizer and compost treatments, respectively 89.11 g and 82.11 g.